Preparation method of temperature stimulation deformation reversible response soft robot polymer
By preparing temperature-stimulating soft robot polymers with three-dimensional pore structures, the problem of small driving deformation in the prior art is solved, the bidirectional extension-shrink drive performance of porous polymers is improved and multifunctional, and the application in the field of flexible drivers is expanded.
Patent Information
- Application Number
- CN202411715464.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Existing intelligent bionic software robots face the problem of small driving deformation, and it is difficult to achieve different driving performance and varying degrees of reversible deformation in complex driving environments.
By designing and preparing a temperature-stimulating soft robot polymer with a three-dimensional pore structure, the solution blending polymerization is performed using linear semi-crystalline polymers and peroxide initiators, the pore size is adjusted by combining particle leaching method to form an entangled mesh crosslinking network and crystalline network structure, and the temperature stimulation deformation reversible response is achieved.
It improves the bidirectional stretch-retractable driving performance of porous polymers, realizes the regulation and multifunctionalization of driving performance, and expands cutting-edge applications in the field of flexible drivers.
Smart Images

Figure CN119505345A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft robot polymers, and in particular to a method for preparing a soft robot polymer that can reversibly respond to temperature stimulation and deformation. Background Art
[0002] Nowadays, porous polymers have potential important application value in various fields. For example, intelligent porous driving materials that reduce the impact of collisions and are soft to deform, highly sensitive porous sensing materials that change their structure significantly under very small pressure and transmit obvious electrical signals, porous adsorption materials that can transport liquids autonomously, and porous structures that can provide gas and liquid permeability provide a good solution for optimizing stimulus response functions. Studies have found that the driving strain of polymers with porous structures is much larger than that of solid and non-porous structures. This may be related to the complex stress distribution in compressed open-pore polymers. If the pore is regarded as a simple spring, compression along a longer path will produce higher spring energy storage, and the anisotropic pore structure will change greatly along the direction of high pore length. In addition, the mechanical response deformation mechanism of low-strain and high-strain pores is different. The pore wall bends, twists and buckles in different directions, and their stresses interact, making porous polymers have greater deformation driving ability than solid structural materials.
[0003] The porous polymer developed with stimulus-responsive reversible deformation function not only has continuous, reciprocating "contraction-expansion" motion, but also has the lightness, softness, superelasticity, high compressibility of the porous structure, and self-contraction and self-expansion like a sponge, and reversible motion back and forth. However, how to regulate the flexible structure and design method of stimulus-responsive reversible porous polymer to construct the deformation space and achieve different driving performance and different degrees of reversible deformation to cope with complex driving environments is still a challenge. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of small driving deformation faced by intelligent bionic soft robots in the prior art, and proposes a method for preparing a temperature-stimulated soft robot polymer that can reversibly respond to deformation. By designing and preparing a temperature-stimulated soft robot polymer with a three-dimensional pore structure, the pore structure is precisely controlled from the structural design aspect, thereby achieving improvement and regulation of the bidirectional extension-contraction driving performance of the porous polymer, and further expanding the cutting-edge applications in the field of the new generation of flexible actuators.
[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a soft robot polymer that can reversibly respond to temperature stimulation and deformation. The method comprises the following steps: using linear semi-crystalline polymer polyethylene vinyl acetate and peroxide initiator benzoyl peroxide to carry out solution blending polymerization as a soft robot polymer matrix; using particle leaching to form pores in a polymer semi-crystalline system, adjusting the particle size parameters of the porogen to design the three-dimensional pore structure characteristics and pore morphology; finally, the linear molecules are bonded and bridged to form a tangled mesh cross-linked network and a crystalline network structure to form a soft robot polymer that can reversibly respond to temperature stimulation and deformation.
[0006] The present invention uses a microscopic cross-linked network and a semi-crystalline structure as a matrix to construct a deformation space by regulating a macroscopic three-dimensional pore structure, thereby achieving improved driving performance and multifunctional driving.
[0007] Preferably, the process of the solution blending polymerization is: dissolving a quantitative polyethylene vinyl acetate copolymer and 8 wt% benzoyl peroxide in xylene, and sealing and uniformly stirring with magnetic force at 90°C for 12 h until the polyethylene vinyl acetate and the initiator benzoyl peroxide are completely dissolved in the xylene to obtain a polymer-initiator mixed solution.
[0008] Preferably, the particle leaching method is to add glucose particles to a polyethylene vinyl acetate polymer mixture, and stir the mixture at a constant speed of 80°C in a fume hood for 6 hours. To obtain a complete pore wall with uniform pore distribution and no large-area fractures, it is necessary to control the rotation speed and stir sufficiently, and slowly evaporate the xylene solvent, so that the glucose particles are not easily accumulated at the bottom of the cup, and finally obtain a uniformly dispersed polymer-initiator-glucose particle mixture.
[0009] Preferably, the solvent ratio of the polyethylene vinyl acetate polymer to the xylene organic solvent is 1:5, the mass percentage ratio of the polyethylene vinyl acetate polymer to the glucose particles is 1:6, and the particle sizes of the glucose particles are 50 μm, 110 μm, 160 μm, and 450 μm, respectively.
[0010] Preferably, the pore making process is as follows: pouring the polymer-initiator-glucose particle mixture into a rectangular parallelepiped mold, placing it in a high-temperature vacuum oven at 80°C for 24 hours, waiting for the organic solvent to slowly and completely evaporate, and then placing it in a 60°C oven for 8 hours to remove the residual solvent to obtain a polymer-initiator-glucose particle composite material block.
[0011] Preferably, the bridging reaction process is: placing the prepared composite material block into a vacuum tube furnace for bridging reaction, taking out the polymer-initiator-glucose particle composite material block after the reaction is completed, and soaking it in 35°C distilled water for 48 hours to dissolve the glucose particles, during which the distilled water is replaced 5-6 times to obtain temperature-stimulated soft robot polymers with different pore structure characteristics, which are P-50, P-110, P-160 and P-450 respectively.
[0012] Preferably, the bridging reaction temperature is 300 °C, the reaction time is 5 h, and the nitrogen flow rate is 80 mL / min; the four different pore densities are 0.1865 g / cm 3 , 0.1775 g / cm 3 , 0.1529 g / cm 3 and 0.1434 g / cm 3 .
[0013] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention has made useful explorations in the preparation method. By adjusting the size of the pore-forming particles to control different pore structures and pore sizes, a temperature-stimulated soft robot polymer with adjustable driving strain, adjustable structure and structural flexibility is prepared to meet different driving requirements in the field of thermal braking intelligent soft materials.
[0014] 2. The present invention achieves lightweighting of polymers (density less than 0.15 g / cm 3 ) and softness (stiffness less than 0.2 N / mm 2 ), and has a direct effect on the increase of driving strain (increasing strain by 5%), and the constructed soft robot polymer has deformation reversible stability.
[0015] 3. The present invention uses particle leaching method to adjust the pore size to achieve different bidirectional driving performance regulation, which has not been studied by researchers and belongs to an unexplored field. The present invention's method for regulating pore structure is simple, mild, smart, low-cost, and easy to prepare controllable pore size and porosity, realizing multifunctional driving. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a preparation flow chart of the present invention; Figure 2 Schematic diagram of the thermomechanical analysis (TMA) bidirectional reversible drive and recovery cycle curve of the sample in Example 1 of the present invention (①-② driving contraction, ②-③ recovery expansion); Figure 3 The bidirectional driving performance curves of samples with different pore structure characteristics in Example 1 and Example 4 of the present invention under three cycles of cooling-heating; Figure 4 The bidirectional driving performance curve and deformation driving-recovery performance comparison diagram of samples with different pore structure characteristics in Example 1 and Example 4 of the present invention under 10 cycles of cooling-heating; Figure 53D X-ray μCT photos of different pore structure characteristics in samples of Examples 1, 2, 3, and 4 of the present invention. DETAILED DESCRIPTION
[0017] For a better understanding of the present invention, the following examples are further descriptions of the present invention.
[0018] The present invention uses a cross-linked semi-crystalline network molecular structure as a polymer matrix, and through precise design and regulation of the macroscopic three-dimensional pore structure characteristics and pore morphology, achieves improvement in the bidirectional extension-contraction driving performance of the soft robot polymer, structural adjustability, and multifunctional driving.
[0019] Embodiment 1: A method for preparing a temperature-stimulated deformation reversibly responsive soft robot polymer comprises the following steps: dissolving a quantitative amount of 10 g of linear semi-crystalline polymer polyethylene vinyl acetate and 0.87 g of peroxide initiator benzoyl peroxide in 50 mL of xylene, and sealing the mixture under uniform magnetic stirring at 90°C for 12 h until the polyethylene vinyl acetate polymer and the initiator benzoyl peroxide are completely dissolved in the xylene to obtain a polymer-initiator mixed solution; adding 60 g of glucose particles with a particle size of 50 μm to the polymer-initiator mixed solution, and uniformly stirring the mixture under magnetic stirring at 80°C in a fume hood for 6 h to obtain a uniformly dispersed polymer-initiator-glucose particle mixed solution; pouring the polymer-initiator-glucose particle mixed solution into a rectangular parallelepiped mold, placing the mixture in a high-temperature vacuum oven at 80°C for 24 h, and slowly and completely evaporating the organic solvent, and then placing the mixture in an oven at 60°C for 8 h to remove the residual solvent to obtain a polymer-initiator-glucose particle composite material block; placing the prepared composite material in a 300 The bridging reaction was carried out in a vacuum tube furnace at 35°C for 5 hours. After the reaction, the polymer-initiator-glucose particle composite material was immersed in 35°C distilled water for 48 hours to dissolve the glucose particles, thereby obtaining the temperature-stimulated soft robot polymer P-50.
[0020] Embodiment 2: A method for preparing a temperature-stimulated deformation reversibly responsive soft robot polymer comprises the following steps: dissolving a quantitative amount of 10 g of linear semi-crystalline polymer polyethylene vinyl acetate and 0.87 g of peroxide initiator benzoyl peroxide in 50 mL of xylene, and sealing the mixture under uniform magnetic stirring at 90°C for 12 h until the polyethylene vinyl acetate polymer and the initiator benzoyl peroxide are completely dissolved in the xylene to obtain a polymer-initiator mixed solution; adding 60 g of glucose particles with a particle size of 110 μm to the polymer-initiator mixed solution, and uniformly stirring the mixture under magnetic stirring at 80°C in a fume hood for 6 h to obtain a uniformly dispersed polymer-initiator-glucose particle mixed solution; pouring the polymer-initiator-glucose particle mixed solution into a rectangular parallelepiped mold, placing the mixture in a high-temperature vacuum oven at 80°C for 24 h, and slowly and completely evaporating the organic solvent, and then placing the mixture in an oven at 60°C for 8 h to remove the residual solvent to obtain a polymer-initiator-glucose particle composite material block; placing the prepared composite material in a 300 The bridging reaction was carried out in a vacuum tube furnace at 35°C for 5 hours. After the reaction, the polymer-initiator-glucose particle composite material was immersed in 35°C distilled water for 48 hours to dissolve the glucose particles, thereby obtaining the temperature-stimulated soft robot polymer P-110.
[0021] Embodiment 3: A method for preparing a temperature-stimulated deformation reversibly responsive soft robot polymer comprises the following steps: dissolving a quantitative amount of 10 g of linear semi-crystalline polymer polyethylene vinyl acetate and 0.87 g of peroxide initiator benzoyl peroxide in 50 mL of xylene, and sealing the mixture under uniform magnetic stirring at 90°C for 12 h until the polyethylene vinyl acetate polymer and the initiator benzoyl peroxide are completely dissolved in the xylene to obtain a polymer-initiator mixed solution; adding 60 g of glucose particles with a particle size of 160 μm to the polymer-initiator mixed solution, and uniformly stirring the mixture under magnetic stirring at 80°C in a fume hood for 6 h to obtain a uniformly dispersed polymer-initiator-glucose particle mixed solution; pouring the polymer-initiator-glucose particle mixed solution into a rectangular parallelepiped mold, placing the mixture in a high-temperature vacuum oven at 80°C for 24 h, and slowly and completely evaporating the organic solvent, and then placing the mixture in an oven at 60°C for 8 h to remove the residual solvent to obtain a polymer-initiator-glucose particle composite material block; placing the prepared composite material in a 300 The bridging reaction was carried out in a vacuum tube furnace at 35°C for 5 hours. After the reaction, the polymer-initiator-glucose particle composite material was immersed in 35°C distilled water for 48 hours to dissolve the glucose particles, thereby obtaining the temperature-stimulated soft robot polymer P-160.
[0022] Embodiment 4: A method for preparing a temperature-stimulated deformation reversibly responsive soft robot polymer comprises the following steps: dissolving a quantitative amount of 10 g of linear semi-crystalline polymer polyethylene vinyl acetate and 0.87 g of peroxide initiator benzoyl peroxide in 50 mL of xylene, and sealing the mixture under uniform magnetic stirring at 90°C for 12 h until the polyethylene vinyl acetate polymer and the initiator benzoyl peroxide are completely dissolved in the xylene to obtain a polymer-initiator mixed solution; adding 60 g of glucose particles with a particle size of 450 μm to the polymer-initiator mixed solution, and uniformly stirring the mixture under magnetic stirring at 80°C in a fume hood for 6 h to obtain a uniformly dispersed polymer-initiator-glucose particle mixed solution; pouring the polymer-initiator-glucose particle mixed solution into a rectangular parallelepiped mold, placing the mixture in a high-temperature vacuum oven at 80°C for 24 h, and allowing the organic solvent to slowly and completely evaporate, and then placing the mixture in an oven at 60°C for 8 h to remove the residual solvent to obtain a polymer-initiator-glucose particle composite material block; placing the prepared composite material in a 300 The bridging reaction was carried out in a vacuum tube furnace at 35°C for 5 hours. After the reaction, the polymer-initiator-glucose particle composite material was immersed in 35°C distilled water for 48 hours to dissolve the glucose particles, thereby obtaining the temperature-stimulated soft robot polymer P-450.
[0023] Performance Testing 1. Thermomechanical analysis-bidirectional reversible driving performance test The thermomechanical curves of the bidirectional driving performance of samples with different pore structure characteristics under three cycles of cooling-heating are obtained by testing Examples 1 and 4. The test results are as follows: Figure 3 As shown in the figure, the different bidirectional reversible actuation and recovery strain are mainly attributed to the different pore structures. P-50 with the smallest pore size has stronger bidirectional reversible actuation performance (>5%) and shape recovery performance (>98%). Figure 4 The curves of 10 long-term highly repeatable bidirectional reversible driving and recovery cycles are shown, which proves the stability and repeatability of the temperature-stimulated reversible deformation driving of the polymer of the soft robot. Figure 4 Generally, the first drive-recovery cycle usually leads to poor deformation response performance and cannot reflect the true bidirectional reversible drive state. However, after the first heating-cooling cycle, the reversible drive contraction-recovery expansion performance tends to be stable and tends to be stable with the increase of the number of thermomechanical cycles. This may be because the first heating-cooling cycle is equivalent to annealing and elimination of thermal history process, which is related to the crystallization behavior of the material itself.
[0024] 2. 3D X-ray tomography test The three-dimensional X-ray tomography (3D X-ray μCT) images of different pore structure characteristics were obtained by testing Examples 1, 2, 3, and 4. Figure 5 As shown in the figure, the brown area in the CT scan image represents the pore wall, and it can be seen that the pores gradually decrease (from Figure 5 a to 5d). Figure 5 a It can be seen from Example 4 that the sponge-like polymer has a relatively loose pore skeleton structure and a significantly larger pore size. Figure 5 d It can be seen that the polymer of Example 1 has a dense pore skeleton structure and the pore size is the smallest.
[0025] In summary, the present invention regulates the macro-scale pore structure characteristics, constructs a temperature-stimulated soft robot polymer diversified deformation space, controls the heat transfer path, improves the bidirectional reversible extension-contraction driving performance, and further expands the cutting-edge applications in the new generation of flexible self-driving fields.
[0026] The above is only a preferred embodiment of the present invention. It should be noted that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be considered as the protection scope of the present invention.
Claims
1. A method for preparing a temperature-stimulated reversible deformation-responsive soft robot polymer, characterized in that: Linear semi-crystalline polymer polyethylene vinyl acetate and peroxide initiator benzoyl peroxide are used for solution blending polymerization as the polymer matrix of soft robots; the particle leaching method is used to make pores in the polymer semi-crystalline system, and the three-dimensional pore structure characteristics and pore morphology are designed by adjusting the particle size parameters of the porogen; finally, the linear molecules bond and bridge with each other to form a tangled mesh cross-linked network and a crystalline network structure of a soft robot polymer with reversible response to temperature stimulation deformation.
2. The method for preparing a temperature-stimulated deformation reversibly responsive soft robot polymer according to claim 1, characterized in that: The process of the solution blending polymerization is as follows: a quantitative polyethylene vinyl acetate copolymer and 8 wt% benzoyl peroxide are dissolved in xylene, and the mixture is sealed and uniformly magnetically stirred at 90° C. for 12 h until the polyethylene vinyl acetate and the initiator benzoyl peroxide are completely dissolved in the xylene to obtain a polymer-initiator mixed solution.
3. The method for preparing a temperature-stimulated deformation reversibly responsive soft robot polymer according to claim 2, characterized in that: The particle leaching method is to add glucose particles to the polymer-initiator mixture, stir it uniformly at 80°C in a fume hood with magnetic stirring for 6 hours, and control the speed to fully stir it, so that the xylene solvent evaporates slowly, so that the glucose particles are not easy to accumulate at the bottom of the cup, and finally a uniformly dispersed polymer-initiator-glucose particle mixture is obtained.
4. The method for preparing a temperature-stimulated deformation reversibly responsive soft robot polymer according to claim 3, characterized in that: The ratio of polyethylene vinyl acetate to xylene organic solvent is 1:5, the mass percentage ratio of polyethylene vinyl acetate to glucose particles is 1:6, and the particle sizes of the glucose particles are 50 μm-450 μm respectively.
5. The method for preparing a temperature-stimulated deformation reversibly responsive soft robot polymer according to claim 3, characterized in that: The pore making process is as follows: pouring a polymer-initiator-glucose particle mixture into a rectangular parallelepiped mold, placing it in a high-temperature vacuum oven at 80°C for 24 hours, waiting for the organic solvent to slowly and completely evaporate, and then placing it in a 60°C oven for 8 hours to remove the residual solvent to obtain a polymer-initiator-glucose particle composite material block.
6. The method for preparing a temperature-stimulated reversibly responsive soft robot polymer according to claim 5, characterized in that: The bridging reaction process is as follows: placing the prepared composite material block into a vacuum tube furnace for bridging reaction, taking out the polymer-initiator-glucose particle composite material block after the reaction is completed, and soaking it in 35° C. distilled water for 48 hours to dissolve the glucose particles, during which the distilled water is replaced 5-6 times to obtain temperature-stimulated soft robot polymers with different pore structure characteristics.
7. The method for preparing a temperature-stimulated deformation-reversible response soft robot polymer according to claim 1, characterized in that: The bridging reaction temperature was 300 °C, the reaction time was 5 h, and the nitrogen flow rate was 80 mL / min.
Citation Information
Patent Citations
Soft cross-linked polyethylene insulating material
CN101602870A
Self-repair material and article with shape memory effect and preparation method thereof
CN106633721A
Preparation method of ethylene-vinyl acetate copolymer porous shape memory material
CN113265088A
Cited By
Preparation method for improving driving performance of stimuli-responsive polymer film
CN121021886A